2014
DOI: 10.1134/s0018151x14030055
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of plasma of dielectric barrier discharge at atmospheric pressure with a liquid electrode

Abstract: The composition of active particles in a plasma was calculated for the conditions of dielectric bar rier discharge at atmospheric pressure in oxygen from the measured waveforms of current and voltage using joint solution of the Boltzmann equation and the equations of chemical kinetics. Kinetic equations included the reactions involving O 2 and H 2 O molecules (the main plasma gas), their dissociation products, and the excited states of molecules O 2 and atoms O. It is shown that the main neutral components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…1 are described well by this relation ship with R 2 = 0.95-0.98 and rate constants of 0.059 ± 0.003, 0.064 ± 0.006, 0.096 ± 0.007, and 0.136 ± 0.012 s -1 at discharge powers of 0.4, 1.2, 2.1, and 4 W, respectively. The increase in the rate constants with increasing power is not surprising, since our study [21] devoted to the simulation of the gas phase of such a reactor has revealed that an increase in power leads to an increase in the concentration of all active plasma species. Note that the rate constant found in [13] for direct current (40 mA) discharge in air was an order of magnitude lower to be (4.78 ± 0.75) × 10 -3 s -1 .…”
Section: Resultsmentioning
confidence: 77%
“…1 are described well by this relation ship with R 2 = 0.95-0.98 and rate constants of 0.059 ± 0.003, 0.064 ± 0.006, 0.096 ± 0.007, and 0.136 ± 0.012 s -1 at discharge powers of 0.4, 1.2, 2.1, and 4 W, respectively. The increase in the rate constants with increasing power is not surprising, since our study [21] devoted to the simulation of the gas phase of such a reactor has revealed that an increase in power leads to an increase in the concentration of all active plasma species. Note that the rate constant found in [13] for direct current (40 mA) discharge in air was an order of magnitude lower to be (4.78 ± 0.75) × 10 -3 s -1 .…”
Section: Resultsmentioning
confidence: 77%
“…5). This result is quite expected, since an increase in power leads to an increase in the rates of formation of almost all active particles, as well as the average energy and concentration of electrons [34].…”
Section: Resultsmentioning
confidence: 79%
“…Dielectric barrier discharges (DBD) caused the following changes in the infrared spectra of ilmenite: there was an increase in the relative intensities of the lines corresponding to vibrations of Ti−O bonds in TiO6−octahedra. The relative intensities of the lines of −O−O− peroxo groups grew as well, due likely to the oxidation of the mineral surfaces under the action of products (e.g., O3, H2O2, NO, N2O [15,21]) of DBD low-temperature plasma (LPT). As the duration of treatment (ttreat) grew, so did the intensity of the lines associated with water molecules adsorbed on the mineral surfaces.…”
Section: Resultsmentioning
confidence: 99%